Sociolinguistic Competence As An Autonomous Component Of Communicative Competence - Ermirzayev Abbos Vakhobjonovich (Periodica Journal, 2025)
This article provides information about sociolinguistic competence, which is an essential component of communicative competence
Keywords: sociolinguistic; competence; communicative